1993
DOI: 10.1007/bf02261005
|View full text |Cite
|
Sign up to set email alerts
|

The urate and xanthine concentrations in the cerebrospinal fluid in patients with vascular dementia of the Binswanger type, Alzheimer type dementia, and Parkinson's disease

Abstract: We determined the urate and xanthine concentrations in the cerebrospinal fluid (CSF) in patients with vascular dementia of the Binswanger type (VDBT), Alzheimer type dementia (ATD), and Parkinson's disease (PD). We found that the urate concentration was significantly increased in VDBT patients, but significantly decreased in ATD patients compared with controls. The ratio of the concentrations of uric acid (UCSF) to xanthine (XCSF) in the CSF (UCSF/XCSF) had a significant correlation with the ratio of the UCSF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 26 publications
2
38
1
2
Order By: Relevance
“…It is therefore possible that the uric acid decline in AD brain reflects, or possibly contributes to, AD-related neurodegeneration. One previous study reports decreased uric acid in AD CSF (Tohgi et al, 1993), whereas another reports increased uric acid in AD CSF (Degrell and Niklasson, 1988). Measurements of serum uric acid in AD are similarly contradictory (Maesaka et al, 1993;Ahlskog et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…It is therefore possible that the uric acid decline in AD brain reflects, or possibly contributes to, AD-related neurodegeneration. One previous study reports decreased uric acid in AD CSF (Tohgi et al, 1993), whereas another reports increased uric acid in AD CSF (Degrell and Niklasson, 1988). Measurements of serum uric acid in AD are similarly contradictory (Maesaka et al, 1993;Ahlskog et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…The association of low-normal serum urate levels with Parkinson's disease and multiple sclerosis has led to proposals that higher PUA protects neurons from toxic effects of peroxynitrite (7,(41)(42)(43). However, urate concentration in brain is much lower than in plasma (7,44,45); urate is a poor scavenger of peroxynitrite (46)(47)(48); and reactions of urate with free radicals have pro-as well as antioxidant consequences (46,47,49,50). Moreover, significantly raising serum urate concentration for 2 years was of no benefit in patients with relapsing-remitting multiple sclerosis (51).…”
Section: Discussionmentioning
confidence: 99%
“…A postmortem study of 4 PD cases showed decreased levels of uric acid in substantia nigra compared to controls [655]. Another study of 11 PD cases found no differences in cerebrospinal fluid levels of uric acid between cases and controls [656].…”
Section: Uric Acid and Goutmentioning
confidence: 98%